A Design Management Tool for Product Development in SMEs: The Integrated Design Management (IDM) Tool - Vitor Carneiro; Augusto Barata da Rocha; Bárbara Rangel; Jorge Lino Alves (She Ji: The Journal of Design, Economics and Innovation, 2025)
Compelling evidence highlights the importance of good design in driving company success. However, in manufacturing small and medium-sized enterprises (SMEs), good design practices and competencies are frequently marginalized. Given the critical role of SMEs in any economy, the new product development (NPD) process must be managed in a structured way. Yet current design management tools often fail to show how SMEs can implement design management effectively. This article introduces the Integrated Design Management (IDM) Tool, which comprises two components: an audit and a checklist with integrated progress monitoring elements. The audit strategically assesses a company’s integration process and design management capabilities, aiming to position design as a core component of an organization’s vision and strategy. Operationally, the checklist provides a structured framework for planning and monitoring NPD projects—emphasizing objectives, actions, and outputs—and enabling companies to self-assess and take actions to improve. Developed iteratively across four phases—Exploratory Study, Tool Creation and Feasibility, Tool Development, and Validation—the tool involved active participation from five manufacturing SMEs through an action research approach grounded in evidence from the literature and exploratory and validation studies. This collaborative approach supported the development of a robust tool while contributing to improved design practices in new product development and manufacturing.